Spring framework master class : beginner to expert - Karanam, Ranga (Packt Publishing, 2018)
"Learn the magic of the Spring framework from IOC (Inversion of Control), DI (Dependency Injection), and Application Context, to the world of Spring Boot, AOP, JDBC and JPA. Get set for an incredible journey. In this course, you will learn the features of the Spring and Spring Modules: JDBC, AOP, Data JPA with a hands-on, step-by step-approach. You will be introduced to Spring Boot, Unit Testing with JUnit and Mockito, talking to the database with Spring JDBC and JPA, Maven (dependencies management), Eclipse (IDE), and the Tomcat Embedded Web Server. We will help you set up each one of these. You will learn step-by-step about Spring in more than 100 steps. This course would be a perfect first step as an introduction to Spring."--Resource description page